Quantitative rate measurement of the hydroxide driven dissolution of an enteric drug coating using atomic force microscopy - Sanders, G; Booth, J; Compton, R (1997)
The hydroxide-driven dissolution of the polymer hydroxypropyl methylcellulose phthalate (HPMCP) in aqueous solution is studied using atomic force microscopy. The novel technique of employing the surface-averaged z-piezo voltage as a direct measure of the mean absolute surface height is described, so as, after appropriate calibration, to permit the ready inference of dissolution fluxes. In the case of interest the following dissolution rate law was established: j/g·cm-2·s-1 = 105.0[OH-] over the pH range 8.0-9.2, where j is the flux of the dissolving polymer and [OH-] is measured in mol cm-3.